Modal Analysis of Driven Part of Globoid Indexing Cam Mechanism based on ANSYS - Li Chengping; Ge Zhenghao; Zhang Xingyu; Zhang Shuanglin (Jixie chuandong)
The natural frequency and modal analysis of globoid indexing cam mechanism are studied.Through the establishment of equivalent mass dynamics model of the globoid indexing cam mechanism,the force condition is analyzed and the equation of six order modal natural frequency is deduced. Combining with the example,the modal analysis process and step of the globoid indexing cam mechanism are introduced,and the foundation for avoiding the resonance during the further design of globoid indexing cam mechanism is provided.